Human iPSC-derived retinal organoids develop robust Alzheimer’s disease neuropathology - James, Ethan; Vielle, Anne; Cusato, Karen; Li, Helen; Lee, Byoungin; Parween, Shama; Howell, Anna; Johnson, Noah R.; Chial, Heidi J.; Potter, Huntington; Vergara, M. Natalia (Frontiers in Cellular Neuroscience, 2024)
Alzheimer’s disease (AD), characterized by memory loss and cognitive decline, affects nearly 50 million people worldwide. Amyloid beta (Aβ) plaques and intracellular neurofibrillary tangles (NFTs) of phosphorylated Tau protein (pTau) are key histopathological features of the disease in the brain, and recent advances have also identified AD histopathology in the retina. Thus, the retina represents a central nervous system (CNS) tissue highly amenable to non-invasive diagnostic imaging that shows promise as a biomarker for early AD. Given the devastating effects of AD on patients, their families, and society, new treatment modalities that can significantly alter the disease course are urgently needed. In this study, we have developed and characterized a novel human retinal organoid (RO) model derived from induced pluripotent stem cells (iPSCs) from patients with familial AD due to mutations in the amyloid precursor protein gene (APP). Using immunofluorescence and histological staining, we evaluated the cellular composition and AD histopathological features of AD-ROs compared to control ROs from healthy individuals. We found that AD-ROs largely resemble their healthy control counterparts in cellular composition but display increased levels of Aβ and pTau. We also present proof of principle of an assay to quantify amyloid levels in whole ROs. This in vitro model of the human AD retina constitutes a new tool for drug screening, biomarker discovery, and pathophysiological studies.